Prevalence with precise diagnosis of Hepatitis-Hydropericardium Syndrome (HHS) in broiler chicken in eastern Bangladesh - Md Masuk Rahman Kingshuk; Md Shajedur Rahman; Nazmi Ara Rumi; Mst Aireen Akter; Hemayet Hossain; Md Nurnoby Islam (Veterinary Integrative Sciences)
Hepatitis-Hydropericardium Syndrome (HHS) is an increasingly prevalent poultry disease, particularly affecting broiler chickens in Bangladesh. HHS is caused by Fowl Aviadenovirus Serotype 4 (FAdV-4), characterized by the accumulation of clear or yellowish-brown fluid in the pericardium. This study, conducted over one year from March 2022 to February 2023, examined a total of 109,000 broiler birds to assess the prevalence and precise diagnosis of HHS. Diagnosis was performed systematically and ethically through physical and clinical examinations, including the evaluation of clinical symptoms and post-mortem lesions. The presence of the causal agent was confirmed via polymerase chain reaction (PCR) from liver and kidney samples, using FAdV-specific primers targeting the hexon-b gene. The study found an overall prevalence of HHS in broilers to be 10.55% (95% CI: 10.37-10.73). The disease was infrequently observed in birds younger than two weeks, with the highest prevalence noted between two to three weeks of age (15.31%). Seasonally, HHS incidence was higher during the summer (13.92%) and rainy season (12.86%), while it was significantly lower in the winter (4.35%). The case fatality rate was determined to be 58.77%, with an average mortality rate of 6.20%. These findings provide critical insights for the poultry industry in Bangladesh, enabling the development of effective strategies for the prevention and control of HHS